Baghdad’s Fall and Its Aftermath: Contesting the Central Asian Political Background and the Emergence of Islamic Mongol Dynasties - Muhammad Abdul Karim (Al-Jami'ah: Journal of Islamic Studies, 2018)
The sack of Baghdad is a dramatic event which was immediately followed by several key historical events, including the rise of Islamic Mongol. Founded by Chengiz Khan, the Mongol are the destroyer machine who previously ended the glory of Islam in 13th century Middle East. A lot has been said concerning that dramatic siege, but little has been discussed regarding the continuation between the siege and the “reverse flow” of the Mongols as the unique events in the aftermath of the Baghdad’s fall. The object of this paper is to examine the siege of Baghdad in the light of Central Asian frame and to explore the important events in the aftermath of the siege which are related to the rise of the Islamic Mongol Dynasties. [ Jatuhnya Baghdad merupakan peristiwa tragis yang diikuti oleh sejumlah peristiwa lain, termasuk munculnya kerajaan Mongol Islam. Dibawah kepemimpinan Chengisz Khan, Mongol berhasil menggantikan kejayaan Islam di Timur Tengah abad ketigabelas. Banyak studi yang telah mengkaji  peralihan tersebut, namun sedikit yang membahas kelanjutan proses tersebut dan arus balik Mongol pasca jatuhnya Baghdad. Artikel ini membahas peralihan Baghdad dibawah konstelasi Asia Tengah dan peristiwa penting dibalik pendudukan Mongol hingga munculnya dinasti Islam Mongol.]